1987
DOI: 10.1084/jem.166.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human B cell stimulatory factor 1 receptor.

Abstract: 125I-labeled recombinant human B cell stimulatory factor 1 (BSF-1) was used to characterize receptors specific for this lymphokine on in vitro cell lines representing human B, T, and hematopoietic lineages, as well as on adherent cell lines of epithelial and endothelial origin, and on primary human gingival fibroblasts. BSF-1 binding was extremely rapid and saturable at both 4 and 37 degrees C, with a slow dissociation rate. On all human cell types examined, BSF-1 bound to a single class of high-affinity recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
1
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(72 citation statements)
references
References 38 publications
8
60
1
3
Order By: Relevance
“…However, our FCCS experiments demonstrated that the two-dimensional dissociation constants of the IL-4R complexes are of the order of several hundred to a thousand receptors per µm 2 (Gandhi et al, 2014). At endogenous IL-4R cell surface densities of 1-10 receptors per µm 2 (Lowenthal et al, 1988;Ohara and Paul, 1987;Park et al, 1987), the fraction of subunits entering active heterodimers would thus be negligible even with saturating ligand levels. Productive signalling therefore demands a subcellular concentration step that is missing from current models of CKR activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our FCCS experiments demonstrated that the two-dimensional dissociation constants of the IL-4R complexes are of the order of several hundred to a thousand receptors per µm 2 (Gandhi et al, 2014). At endogenous IL-4R cell surface densities of 1-10 receptors per µm 2 (Lowenthal et al, 1988;Ohara and Paul, 1987;Park et al, 1987), the fraction of subunits entering active heterodimers would thus be negligible even with saturating ligand levels. Productive signalling therefore demands a subcellular concentration step that is missing from current models of CKR activation.…”
Section: Discussionmentioning
confidence: 99%
“…After selecting regions of interest by analysing GFP immunofluorescence, we identified cortical endosomes within these areas based on their multivesicular ultrastructure and localization. Even though the endogenous cell surface levels of IL-4Rα are very low in most cells (1-10 receptors/µm 2 ) (Lowenthal et al, 1988;Ohara and Paul, 1987;Park et al, 1987), we could detect a specific localized signal (from 10-nm gold particles conjugated to protein A) for the biotinylated IL-4 within these putative cortical endosomes using an anti-biotin antibody (Fig. 4E).…”
Section: Ultrastructural Analysis Of Il-4r Subunit Localization To Comentioning
confidence: 95%
“…IL-4 is the major determinant in directing naive CD4 ϩ T cells to differentiate into Th2 cells (4 -7). It mediates its function by binding and stimulating the IL-4R ␣-chain (8,9). Ligand-bound IL-4R ␣-chain recruits common ␥-chain and its associated kinase Jak3 (10,11).…”
Section: T Helper Type 1 Cells Are Central Immune Components Inmentioning
confidence: 99%
“…It occurs at the relatively low flgure of 150 to 2500 molecules per target cell (CabriJlat et al, 1987;Park et al, 1987). A single dissociation constant of ::::: 100 pM has been determined for the receptor-cytokine interaction.…”
mentioning
confidence: 99%